Underwater Cultural heritage risk assessment methodology for wave-induced hazards: The showcase of the Bay of Cadiz - Fernández-Montblanc, Tomás; Bethencourt, Manuel; Izquierdo, Alfredo (Frontiers in Marine Science, 2022)
Coastal areas are characterized by high energetic conditions associated to the wave transformation process and by numerous underwater cultural heritage (UCH) sites whose preservation is crucial given their cultural and economic value. UCH management requires a decision support system to prioritize UCH interventions and actions for long-term preservation. This paper presents a novel UCH risk assessment methodology to quantitatively assess the impact of wave-induced hazards on UCH in coastal environments at a local level and the screening of UCH sites at risk. The UCH risk is calculated as a function of vulnerability (depending on archaeological materials, slope, and seabed type), hazard (decontextualization, scouring, and erosive wear), and exposure computed for the UCH sites registered in an archaeological database. The procedure was validated at two shipwreck sites, Bucentaure and Fougueux, in the Bay of Cadiz. An agreement between the risk index value and the in situ measurements of the rates of scouring and corrosion (used as a proxy of erosive wear) was observed. The methodology was tested in the Bay of Cadiz using an archaeological database containing 56 UCH sites. It allowed identifying the UCH sites at high risk: six are at risk of decontextualization, four are in peril of scouring erosion, and two are at risk of erosive wear. Two UCH sites at high risk of at least two hazards were also identified. This UCH risk assessment methodology is a stepping stone towards a decision support system that will give priority to research, prospection, management, and protection measures in the UCH sites analyzed to ensure their preservation in a context of climate change in the era of a sustainable blue economy.